Diet-derived circulating antioxidants and risk of knee osteoarthritis, hip osteoarthritis and rheumatoid arthritis: a two-sample Mendelian randomization study - Huang, Li; Xie, Yanqing; Jin, Ting; Wang, Mengqiao; Zeng, Zhen; Zhang, Lina; He, Wenming; Mai, Yifeng; Lu, Jianmeng; Cen, Han (Frontiers in Medicine, 2023)
Objective To examine the causal associations of diet-derived circulating antioxidants with knee osteoarthritis (OA), hip OA, and rheumatoid arthritis (RA) within the two-sample Mendelian randomization (MR) framework. Method Independent single-nucleotide polymorphisms (SNPs) significantly associated with circulating levels of diet-derived antioxidants (retinol, β-carotene, lycopene, vitamin C and vitamin E) were extracted as genetic instruments. Summary statistics of genetic instruments associated with knee OA, hip OA, and RA were obtained from corresponding genome-wide association studies (GWASs). The inverse-variance weighted (IVW) was applied as the primary analysis method, with four sensitivity analysis approaches employed to evaluate the robustness of the primary results. Results Genetically determined per unit increment of absolute circulating levels of retinol was significantly associated with a reduced risk of hip OA [odds ratio (OR) = 0.45, 95% confidence interval (CI) 0.26–0.78, p = 4.43 × 10−3], while genetically determined per unit increase in absolute circulating levels of β-carotene was suggestively associated with increased risk of RA (OR = 1.32, 95% CI 1.07–1.62, p = 9.10 × 10−3). No other causal association was found. Significant evidence for heterogeneity and pleiotropic outlier was only identified when absolute circulating vitamin C was evaluated as the exposure, whereas all sensitive analysis provided consistently non-significant results. Conclusion Our results demonstrated that genetically determined lifelong higher exposure to absolute circulating levels of retinol is associated with a decreased risk of hip OA. Further MR study with more genetic instruments for absolute circulating levels of antioxidants are needed to confirm our results.